PROBLEMS OF FORMATION OF LANGUAGE CULTURE IN ENGLISH LANGUAGE TEACHERS AND FACTORS OF THEIR ELIMINATION - Sultanova, Nargiza (Educational Research in Universal Sciences, 2023)
This article investigates the challenges faced by English language teachers in forming language culture and explores factors contributing to the elimination of these challenges. The research analyzes issues related to language proficiency, pedagogical strategies, cultural sensitivity, and professional development. The findings aim to provide insights for teacher training programs, institutions, and policymakers to enhance language proficiency, cultural awareness, and effective language teaching.